2020
DOI: 10.21037/tau.2019.12.08
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and limitations of current premature ejaculation assessment and diagnostic methods: a review

Abstract: Premature ejaculation (PE) is the most common male sexual dysfunction worldwide.Characteristic symptoms of PE are unexpected, rapid, complete ejaculation, which negatively impacts the sexual act for both sexual partners. Despite the existence of a definitive PE classification system and various diagnostic tools, diagnosing PE is still challenging due to the limitations associated with the assessment of this condition. Hence, it is necessary to review the diagnostic methods and processes of the physical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…They found that men with lifelong PE had significantly higher PEDT scores than men with other types of PE, and lower scores were found among men with premature-like ejaculatory dysfunction. Wei et al 15 state that one single tool is not enough to detect PE. The authors propose the use of tests including penile stimulation to simulate a sexual relationship to obtain objective measures of latency time and intensity of ejaculation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that men with lifelong PE had significantly higher PEDT scores than men with other types of PE, and lower scores were found among men with premature-like ejaculatory dysfunction. Wei et al 15 state that one single tool is not enough to detect PE. The authors propose the use of tests including penile stimulation to simulate a sexual relationship to obtain objective measures of latency time and intensity of ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…These different categorizations make it difficult to compare the studies’ results. 15 In addition, some authors point out the fact that the PEDT is an outdated instrument, as it has not been revised to meet the most current version of the DSM and uses a definition based on expert consensus, not scientific evidence. 59 Moreover, PEDT presents low specificity (50.5%) and positive predictive value (probability of a man actually having PE, given that he has PE according to the PEDT; of 31.2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the most common male sexual dysfunctions, erectile dysfunction (ED; the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance) and premature ejaculation (PE; poorly controlled and rapid ejaculation) greatly affect the quality of life of patients [ 9 , 10 ]. Furthermore, sexual dysfunction is closely associated with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS; urologic pain or discomfort in the pelvic region associated with lower urinary tract symptoms) and is the most common complication [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%